Management of Heart Failure Volume 2: Surgical - Raman, Jai.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2008)
Management of Heart Failure has been conceived as a rapid but comprehensive review for practitioners of all persuasions involved in the management of patients with heart failure. Heart failure is a problem of epidemic proportions in all parts of the world. State of the art treatment may not be accessible to all, but simply creating an awareness of simple methods of diagnosis and treatment would assist in promoting a better global response to this epidemic. This practical volume, written by a panel of world-renown cardiology experts, focuses on the surgical management of heart failure. Surgery for heart failure is an evolving and new area in cardiac surgery with many exciting developments. This volume will be essential reading for all specialists dealing with patients with or who are at risk of heart failure, including but not limited to cardiologists, emergency medicine physicians, critical care physicians, anesthesiologists, interventionalists and cardiothoracic surgeons.
Surgical Perspectives -- Pathophysiology—Clinical Spectrum and Current Management -- Strategies in Surgical Management -- Advanced Heart Failure: Transplant vs Nontransplant Surgical Options -- Transplantation for End-Stage Heart Disease -- OPCAB Treatment for Heart Failure -- Circulatory Support for Bridging to Recovery or Transplantation -- Left Ventricular Reconstruction in Ischemic Cardiomyopathy -- Modifications of the Dor Procedure and Failure Modes of the Procedure -- Mitral Valve Repair -- Destination Therapy with Permanent Mechanical Circulatory Assist Devices -- Enabling Techniques and Technologies -- Catheter-Based and Surgical Therapy for Ventricular Tachycardia -- Catheter Ablation for Atrial Fibrillation in Patients with Heart Failure -- Surgical Therapy for Atrial Fibrillation -- Pacing Therapies, Defibrillators, and Post-Operative Arrhythmias -- Ventricular Containment, Shape Change, and Infarct Restraint -- Other Techniques in Special Circumstances: Pulmonary Thromboendarterectomy in Right Heart Failure -- Surgical Management of Pediatric Heart Failure and Heart Failure due to Congenital Heart Disease -- Anesthetic Management and Hemodynamic Management -- Perioperative and ICU Care, Fluid Management, and Renal Support -- New Therapies and What Is on the Horizon -- Erratum.
Keywords: Cardiology; Cardiac surgery; Surgical transplantation; Internal medicine; Cardiology; Cardiac Surgery; Transplant Surgery; Internal Medicine